Enhancement of Streptomyces aureoverticillatus HN6 through mutagenesis for improved biocontrol of banana wilt disease: an WGS approach - Xiangnan Yan; Shakil Ahmad; Nazia Manzar; Yunfei Zhang; Coline C. Jaworski; Abhijeet Shankar Kashyap; Lanying Wang; Yanping Luo (Chemical and Biological Technologies in Agriculture)
Abstract Fusarium oxysporum-induced Fusarium wilt in bananas is a highly detrimental disease that significantly impedes the progress of the banana industry. In this study, Streptomyces aureoverticillatus HN6 was isolated from soil samples of Hainan Botanical Garden and showed a wide spectrum of bacterial inhibition and a substantial effect on the control of banana wilt disease. While the bacterium demonstrates high inhibitory activity, and the use of live strains is effective, there are limitations in the development and application of this particular strain, such as effective secondary metabolites are difficult to extract; unstable metabolites, and low sporulation rates. Consequently, the strain underwent electron beam mutagenesis, 60Co-γ ray mutagenesis, two cycles of ultraviolet irradiation mutagenesis, and ethyl methanesulfonate (EMS) mutation to generate multiple mutant strains. The mutant strain Z20-1 exhibited resistance to elevated temperatures and enhanced enzymatic activities, specifically increased levels of both amylase and cellulase. Moreover, the fermentation broth of the mutant strain E95 substantially improved the bacterial inhibitory activity. Comparative genomic analysis revealed the presence of seven single-nucleotide polymorphisms (SNPs), one multiple nucleotide polymorphism (MNP), and three insertion-deletions when comparing the mutant strain E95 with the original strain HN6. Notably, the mutant strain E95 exhibited the highest expression of npmC, a core gene in the niphimycin C synthesis gene cluster. Through mutagenesis of the original strain HN6, several mutant strains with superior characteristics were successfully obtained. These findings serve as a valuable technical reference for the mutation breeding of Streptomyces. Graphical Abstract